The Effect of Word-of-Mouth (WOM) and Atmosphere on Competitive Advantage at Rumah Makan Rasa Leluhur, Medan City - Junaedi Caga; Dedy Lazuardi; Irvan Rolyesh Situmorang; Elisabeth Nainggolan; Idina Gustina (Universitas KH. Abdul Chalim Mojokerto, 2026)
The culinary industry in Medan City is growing rapidly, with over 2,002 restaurants operating as of 2025, creating intense competition. Rumah Makan Rasa Leluhur, a traditional restaurant in Medan, faces challenges in maintaining its competitive advantage amid increasing rivalry. This study aims to analyze the effect of Word of Mouth (WOM) and store atmosphere on the competitive advantage of Rumah Makan Rasa Leluhur in Medan City, both partially and simultaneously. This research employed a quantitative associative approach. Data were collected through questionnaires distributed to 100 respondents selected using incidental sampling. The research variables include Word of Mouth (X₁), Store Atmosphere (X₂), and Competitive Advantage (Y). Data analysis was conducted using multiple linear regression, classical assumption tests, t-test, F-test, and coefficient of determination (R²). The results show that Word of Mouth has a positive and significant partial effect on competitive advantage (t = 4.695 > t-table = 1.661; sig. = 0.001) with a partial contribution of 15.5%. Store Atmosphere also has a positive and significant partial effect (t = 4.917 > t-table = 1.661; sig. = 0.001) with a partial contribution of 17.1%. Simultaneously, both variables significantly influence competitive advantage (F = 23.487 > F-table = 3.09; sig. < 0.001), explaining 32.6% of the variance (R² = 0.326). These findings suggest that improving positive word of mouth communication and enhancing the physical store atmosphere are key strategies for strengthening the competitive position of Rumah Makan Rasa Leluhur.